Autologous Peripheral Blood-Derived Orthobiologics for the Management of Shoulder Disorders: A Review of Current Clinical Evidence - Ashim Gupta; Nicola Maffulli (Pain and Therapy)
Abstract Introduction A multidisciplinary approach is recommended to manage shoulder pain, the third most common musculoskeletal disorder, but traditional modalities have limitations, providing only temporary symptomatic pain relief instead of targeting the underlying pathophysiology. Recently, autologous peripheral blood-derived orthobiologics (APBOs) have become popular for the management of shoulder disorders. Platelet-rich plasma (PRP) is the most frequently used APBO, but its efficacy remains disputable. Thus, the possibility of using other APBOs, such as platelet lysate (PL), autologous conditioned serum (ACS), gold-induced cytokine (GOLDIC), plasma rich in growth factors (PRGF), growth factor concentrate (GFC), autologous protein solution (APS), and hyperacute serum (HS), for the management of shoulder disorders have been considered. This review summarizes the outcomes of clinical studies involving APBOs to manage shoulder disorders. Methods Multiple databases (PubMed, Web of Science, Embase, and Scopus) were searched employing terms for APBOs and various shoulder disorders for articles published in the English language to September 11, 2024, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results Only six clinical studies fulfilled our pre-defined search and inclusion criteria. Specifically, one, two, two, and one studies involving the use of PL, ACS, PRGF, and APS, respectively, were included in this review. No clinical studies were identified involving the use of GOLDIC, GFC, and HS. Conclusions Administration of PL, ACS, PRGF, and APS is safe and can reduce pain and improve function in patients with shoulder disorders, including rotator cuff tendinopathy, subacromial impingement syndrome, glenohumeral osteoarthritis and delayed union fracture of the clavicle. Given the dearth of relevant literature and limitations of the available studies, more prospective clinical studies, and ideally, randomized controlled trials, with extended follow-up are necessary to establish the efficacy of APBOs and to select the ideal APBO for the management of shoulder disorders.